2023
DOI: 10.3390/systems11020109
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Evolution and Driving Factors of Regional Green Development: An Empirical Study in Yellow River Basin

Abstract: The sustainable development of the Yellow River Basin (YRB) is regarded as a national strategy for China. Previous literature has focused on the green efficiency measurement of YRB, ignoring its evolution process and influential mechanism. This paper tries to disclose the spatial-temporal evolution of green efficiency and its influential mechanism of the YRB region by proposing a novel integrated DEA-Tobit model to fill the gap. Based on the development path of the YRB region, the multi-period two-stage DEA mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Large-scale tourist activities further increase carbon emission [ 65 ]. This influx introduces high-energy consuming and heavily polluting enterprises, which results in the “pollution paradise” effect [ 66 ], increasing the local ecological environmental pressure and hindering the enhancement of tourism eco-efficiency. In addition, tourism industry agglomeration positively affects tourism eco-efficiency in the Yellow River Basin, which indicates that industrial agglomeration forms technology spillover, learning and competition effects, and promotes the optimal allocation of tourism factors.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale tourist activities further increase carbon emission [ 65 ]. This influx introduces high-energy consuming and heavily polluting enterprises, which results in the “pollution paradise” effect [ 66 ], increasing the local ecological environmental pressure and hindering the enhancement of tourism eco-efficiency. In addition, tourism industry agglomeration positively affects tourism eco-efficiency in the Yellow River Basin, which indicates that industrial agglomeration forms technology spillover, learning and competition effects, and promotes the optimal allocation of tourism factors.…”
Section: Discussionmentioning
confidence: 99%
“…The two-stage DEA method has been applied to real-world problems. Zhou et al [15] proposed a novel integrated DEA-Tobit model, using a multi-period two-stage DEA model to evaluate green development efficiency (GDE) from the provincial and municipal dimensions. Although the DEA-Tobit method is widely used, there has not been any research using network DEA models in evaluating the efficiency of scientific communication.…”
Section: Efficiency Evaluationmentioning
confidence: 99%
“…However, obstacles such as forest cover and the natural population growth rate prevent it from continuing to progress. Wang et al [20] found that the TES levels in the Zhangye Qilian Mountains National Park showed a "U-shaped" trend. At the medium and macro scales, Ruan et al [27] identified that TES levels in the Yangtze River Delta showed an "N" pattern of "rising-declining-rising" and had significant urban heterogeneity.…”
Section: Tourism Ecological Securitymentioning
confidence: 99%
“…However, China's tourism industry has adopted an extensive growth mode, resulting in a severe threat to ecological security, especially in areas with fragile ecosystems, such as arid zones and large river basins. Among them, the Yellow River Basin (YRB), one of the most important ecological barriers in China, has received wide attention from scholars [18][19][20]. It is facing the crisis of ecosystem degradation due to unreasonable tourism development and overtourism [21].…”
Section: Introductionmentioning
confidence: 99%